Evaluasi Manajemen Risiko Tata Kelola TI berbasis COSO ERM Intergrated Framework pada Perguruan Tinggi XYZ - Rahmawati Nurlaela; Suhendi Suhendi (Jurnal Informatika Terpadu, 2021)
Information technology governance (TKTI) risk management is urgently needed by universities because it has many advantages to assist in risk management in the TKTI aspects. Unfortunately, TKTI's risk management at XYZ School of Technology is currently not available. TKTI risk in its current condition is managed manually, incidentally, not holistically, and not based on the concept of a risk management framework. This causes the TKTI system to be not well organized so that carrying out the TKTI maintenance process requires more effort. One application is the application of an online learning system during the Covid-19 pandemic, which causes applications, human resources, and the network used to cause errors often. These errors are either human errors or server failures. This study will discuss the process of Analysis and Design of Information Technology Governance Risk Management at XYZ School of Technology Using the COSO ERM Integrated Framework, which produces TKTI recommendations. The design method is carried out in five stages within the risk management framework, namely the internal environment, goal setting, event identification, risk assessment, and risk response. The framework used to build this risk management module is the COSO ERM Integrated Framework. The results of this study are a TKTI risk management document that makes it easier for the Information System and Technology Agency (BTSI) and the Technical Implementation Unit (UPT) to minimize risk based on events and potential trends, to prevent significant losses at XYZ School of Technology.